THE ROLE OF SUPPLY CHAIN MANAGEMENT IN THE RELATIONSHIP BETWEEN EARNINGS MANAGEMENT AND IDIOSYNCRATIC VOLATILITY - Suhanda, Nopriyanto Hady; Firmansyah, Amrie (International Journal of Supply Chain Management, 2020)
Abstract. This study aims to investigate the association between earnings management and idiosyncratic volatility, as well as the role of supply chain management in moderating the relationship between the two using a quantitative approach. Two kinds of earnings management, real and accrual, are investigated towards idiosyncratic volatility. In measuring supply chain management and real earnings management, this study employs Kothari model and Cohen model, respectively. As for idiosyncratic volatility, it is measured by using the three-factor model by Fama and French. Samples used in this study are Indonesian manufacturing companies listed in the IDX from 2014 to 2017. This study suggests that real and accrual earnings management are positively associated with idiosyncratic volatility. Also, it finds that supply chain improve the relationship between earnings management and idiosyncratic volatility.